Optimization of a solar powered water pump for crop irrigation - Shafiq, Nahian; Navall, Nafisa; Shoshi, Sanjida; Rahman, Afnan Rudabe (BRAC University, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.